Language policy and practice in Eastern Cape courtrooms with reference to interpretation in selected cases - Mpahlwa, Matthew Xola (Rhodes University, Faculty of Humanities, School of Languages, 2015)
This study seeks to find what problems and process of interpreting are experienced by professional interpreters in the criminal justice system in South Africa. This study commences with an outlook of the origins and development of types of interpretation and then proceeds with critical review of scholarly literature dealing with interpretation in multilingual courtroom. This study explores the flawed language policy and its impracticality for the Eastern Cape courtrooms. This study undertakes a critical analysis of the current legislation (Bills & Acts).This study explores the extent to which the court automatic review proceedings act as a gatekeeper in ensuring against prejudice that can result in the non-use and use of indigenous languages in the trial courtroom within the Eastern Cape jurisdiction. Furthermore this study focuses on cases taken for review based on mis-understanding, mis-communication and wrongful interpretation that result in irregularities that appear on court records. This study also investigates the primary barriers for the use of African languages as languages of record in the courtroom. An eclectic sociolinguistic approach which encompasses the ethnography of speaking, and discourse analysis (observation in the courtroom) is used as a methodology in this study. Furthermore, the analysis of case-law forms part of the methodology alongside court observation.This study saw court actors from different spheres of the legal profession give their personal views and encounters with regards the art and the state of court interpreting in the province of the Eastern Cape.This state of affairs may have disastrous and far-reaching effects in that incorrect and/or imperfect translation may relate to the very facts that are crucial for the determination of the case. At the end recommendations are given on how to remedy the current state of affairs.
Keywords: Translating and interpreting; Translating and interpreting -- Errors; Court interpreting and translating -- South Africa -- Eastern Cape; Translators -- Training of -- South Africa -- Eastern Cape